Peculiarities of the influence of high- and low-energy proton and electron irradiations on the characteristics of silicon solar cells - Chernenko, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Experimental data on degradation of photovoltaic and photoenergetic characteristics of silicon solar cells exposed by high-energy electrons and protons as well as low-energy protons have been obtained. The previously proposed theoretical model that can describe degradation of the solar cell characteristics under the influence of irradiation, including that creating spatially inhomogeneous defect distribution over the structure thickness, has been experimentally confirmed. It was ascertained that in the cases of 1 MeV energy electron and 20 MeV energy proton irradiations, when there is a relatively homogeneous defect distribution over the silicon solar cell thickness, its shortcircuit current degrades faster than the open-circuit voltage. On the contrary, in the case of low-energy 0.1 MeV proton irradiation, when the distribution of defects is spatially inhomogeneous, the open-circuit voltage degrades faster than the short-circuit current.